Ernst Feuereisen and Gordon Carruthers - (Author); (Interviewer); (Publisher) (1930)
Photograph - Three men and a canoe loaded with supplies at Pelican Portage, Alberta. Left to right: Ernst Feuereisen, unknown and Gordon Carruthers